A review of igneous and metamorphic saprolites (Journal of Nepal Geological Society, 2000)
Major difficulties in ground engineering works in areas of humid climates arise from the internally heterogeneous and erratically varying zones of weathering profiles developed over igneous and metamorphic rocks as a result of dominantly chemical weathering processes. This paper provides a critical review of recent efforts on improving the description and classification of weathering grades, and discusses current conceptual and practical issues and proposed methods for the engineering geological characterisation of igneous and metamorphic saprolites. Analysis of these issues reveals that lack of comprehensive (geochemical, mineralogical, microfabric, and engineering geological) characterisation studies within well-defined geological frameworks is the underlying reason for failure to define, characterise, and model saprolites as complex engineering geological units and to devise specific site investigation methodologies to explore these complexities.